2009
DOI: 10.3844/ajbbsp.2009.75.83
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Adsorption of the Lead (II) by the Nonliving Biomass Spirogyra neglecta (Hasall) Kützing

Abstract: Problem statement: Conventional techniques for removing dissolved heavy metals are only practical and cost-effective when applied to high strength wastes with heavy metal ion concentrations greater than 100 ppm. The possibility of using a nonliving algal biomass to solve this problem was carried in this study. Lead (II) was used in this study because it had been reported to cause several disorders in human. Approach: The nonliving algal biomass was obtained from a filamentous green alga Spirogyra neglecta. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This result agreed with Murphy et al [37] which reported that metal binding to brown seaweeds showed significant participation of carboxyl group accompanied by interaction of other groups. In fact, the relative importance of these functional groups depend on factors such as the quantity of sites, their accessibility, chemical state and affinity between site and dye [37,38].…”
Section: Sorbent Characterizationmentioning
confidence: 99%
“…This result agreed with Murphy et al [37] which reported that metal binding to brown seaweeds showed significant participation of carboxyl group accompanied by interaction of other groups. In fact, the relative importance of these functional groups depend on factors such as the quantity of sites, their accessibility, chemical state and affinity between site and dye [37,38].…”
Section: Sorbent Characterizationmentioning
confidence: 99%
“…These metals are extremely toxic and harmful even at low concentrations. Thus heavy metal treatment of waste is important in preventing these elements entering our food chains (Hussain et al, 2009). There are several methods for removing heavy metals from wastewater, such as using inverse-phosphor, electrochemical, ion balance, chemical deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Further increase in contact time did not increase the percent (%) adsorption capacity of the metal ions as seen in Figure 2. Hussain et al, (2009) reported initial rapid adsorption and attainment of equilibrium at about 50 mins for sorption of Pb (II) using non-living biomass of Spirogyra neglecta. Similar results have also been reported (Okoronkwo et al, 2008;Okoronkwo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%